METODE BALAI REHABILITASI SOSIAL LANJUT USIA DALAM MENINGKATKAN KESEJAHTERAAN LANJUT USIA DI KECAMATAN BONTOMARANNU KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research focuses on the subject matter of the method of social rehabilitation center for the elderly Gau Mabaji in improving the welfare of the elderly in Bontomarannu sub-district Gowa regency. From the main problem above, the researchers compiled sub-problems that were formulated into two research questions, namely: 1) How are the efforts of the Gau Mabaji social rehabilitation center to improve the welfare of the elderly in Bontomarannu sub-district Gowa regency? 2) What are the obstacles experienced by the Gau Mabaji social rehabilitation in improving the welfare of the elderly in the Bontomarannu district Gowa regency? This type of research is descriptive qualitative research using a social work science approach. The sources of data in this study are primary data sources obtained from social workers and the elderly and secondary data sources obtained from books, journals, scientific papers, research results, documentation, and other documents related to the problems studied. Data collection methods used are observation, interviews, and documentation. The data analysis technique used is data analysis, data presentation, and conclusion drawing. The results of this study indicate that 1). The efforts of the Gau Mabaji social rehabilitation center to improve the welfare of the elderly are: First, services for physical needs such as boarding and consumption services. Second, health services such as health checks and exercise. Third, educational psychosocial services such as tutoring, skills guidance, and counseling. Fourth, is the service of spiritual needs. 2). The inhibiting factors for the Gau Mabaji elderly social rehabilitation center improving the welfare of the elderly are the quality of the existing human resources not all of them have the ability to communicate well with the elderly, the lack of social workers so that they have difficulty in dealing with the elderly, delays in implementing programs for the elderly.